The Role of Maximal Locoregional Block in Autologous Breast Reconstruction. Issue 6 (10th June 2022) - Atwez, Abdelaziz; Martinez, Carlos; Mujadzic, Tarik; Mujadzic, Mirsad; Chen, Elliott; Friedman, Harold I.; Gilstrap, Jarom
Abstract : Background: Enhanced Recovery After Surgery (ERAS) has become the standard of care in microsurgical breast reconstruction. The current literature provides overwhelming evidence of the benefit of ERAS pathways in improving quality of recovery, decreasing length of hospital stay, and minimizing the amount of postoperative narcotic use in these patients. However, there are limited data on the role of using maximal locoregional anesthetic blocks targeting both the abdomen and chest as an integral part of an ERAS protocol in abdominally based autologous breast reconstruction. The aim of this study is to compare the outcomes of implementing a comprehensive ERAS protocol with and without maximal locoregional nerve blocks to determine any added benefit of these blocks to the standard ERAS pathway. Methods: Forty consecutive patients who underwent abdominally based autologous breast reconstruction in the period between July 2017 and February 2020 were included in this retrospective institutional review board–approved study. The goal was to compare patients who received combined abdominal and thoracic wall locoregional blocks as part of their ERAS pathway (study group) with those who had only transversus abdominis plane blocks. The primary end points were total hospital length of stay, overall opioids consumption, and overall postoperative complications. Results: The use of supplemental thoracic wall block resulted in a shorter hospital length of stay in the study group of 3.2 days compared with 4.2 days for the control group ( P < 0.01). Postoperative total morphine equivalent consumption was lower at 38 mg in the study group compared with 51 mg in the control group ( P < 0.01). Complications occurred in 6 cases (15%) in the control group versus one minor complication in the thoracic block group. There was no difference between the 2 groups in demographics, comorbidities, and type of reconstruction. Conclusion: The maximal locoregional nerve block including a complete chest wall block confers added benefits to the standard ERAS protocol in microvascular breast reconstruction.